Implementasi Media Komunikasi Bagi Mahasiswa Perekam Medis Sebagai Penyedia Informasi Kesehatan - Hermawan, Dedy; Apriyanti, Firda; Hatna, Hatna (Jurnal Kesehatan Indonesia, 2024)
This research examines the utilization of communication platforms by medical record students to disseminate health information effectively. In today's information-driven era, especially within healthcare, the role of efficient communication tools is paramount. The study investigates how various media, including social media, electronic health records, and traditional channels, enhance the ability of medical record students to distribute accurate health information. Qualitative methods are employed to analyze the effectiveness of these communication channels in educating the public about health issues. The findings suggest that utilizing these platforms not only enhances students' proficiency in managing health information but also contributes to improving public health literacy. The study underscores the significance of integrating modern communication technologies into health education curricula. This integration is crucial for equipping future healthcare professionals with the skills needed to serve as trustworthy sources of health information.